An overview on recent advances in the synthesis of sulfonated organic materials, sulfonated silica materials, and sulfonated carbon materials and their catalytic applications in chemical processes - Sharghi, Hashem; Shiri, Pezhman; Aberi, Mahdi (Beilstein Journal of Organic Chemistry, 2018)
This review article discusses the progress related to the synthesis and catalytic applications of sulfonated organic materials, sulfonated silica materials, and sulfonated carbon materials for industrial and laboratory products. These catalysts are widely used in acid-catalyzed processes. Most of these acid catalysts are eco-friendly, reusable, and stable. Moreover, the discovery of unique catalysts is vital for developing new, efficient, and reusable catalysts for industrial and laboratory applications. The aim of this review article is to review the recent studies (2014–2018) in the ﬁeld of the utility of sulfonated organic materials, sulfonated silica materials, and sulfonated carbon materials for developing acidic catalysts.
Keywords: acid-catalyzed processes; biodiesel synthesis; sulfonated carbon materials; sulfonated industrial and laboratory products; sulfonated organic materials; sulfonated silica materials

(untitled) - Wilson, K.; Clark, J. H. (Pure Appl. Chem., 2000)

(untitled) - Lee, A. F.; Wilson, K. (Catal. Today, 2015)

The Critical Decade 2013: Climate change science, risks and response 2013. - Steffen, W.; Hughes, L.

(untitled) - Shen, F.; Guo, T.; Bai, C.; Qiu, M.; Qi, X. (Fuel Process. Technol., 2018)

(untitled) - Kundu, S. K.; Bhaumik, A. (ACS Sustainable Chem. Eng., 2015)

(untitled) - De, S.; Dutta, S.; Saha, B. (Catal. Sci. Technol., 2016)

(untitled) - Gernon, M.; Wu, M.; Buszta, T.; Janney, P. (Green Chem., 1999)

(untitled) - Naeimi, H.; Raeisi, A.; Moradian, M. (Arabian J. Chem., 2017)

(untitled) - Kulkarni, P.; Wagh, P.; Zubaidha, P. (Chem. J. (Nottingham, U. K.), 2012)

(untitled) - Sharghi, H.; Aberi, M.; Khataminejad, M.; Shiri, P. (Beilstein J. Org. Chem., 2017)

(untitled) - Sajadikhah, S. S.; Maghsoodlou, M. T.; Hazeri, N.; Habibi-Khorassani, S. M.; Shams-Najafi, S. (Monatsh. Chem., 2012)

(untitled) - Sharghi, H.; Jokar, M. (Synth. Commun., 2009)

(untitled) - Sharghi, H.; Sarvari, M. H. (Tetrahedron, 2003)

(untitled) - Sharghi, H.; Kaboudin, B. (J. Chem. Res., Synop., 1998)

(untitled) - Sharghi, H.; Sarvari, M. H. (J. Chem. Res., 2001)

(untitled) - Sharghi, H.; Jokar, M. (Heterocycles, 2007)

(untitled) - Su, F.; Guo, Y. (Green Chem., 2014)

(untitled) - Mansir, N.; Taufiq-Yap, Y. H.; Rashid, U.; Lokman, I. M. (Energy Convers. Manage., 2017)

(untitled) - Xie, W.; Zhang, C. (Food Chem., 2016)

(untitled) - Thomas, J. M. (Proc. R. Soc. London, Ser. A, 2012)

(untitled) - Vahdat, S. M.; Khaksar, S.; Akbari, M.; Baghery, S. (Arabian J. Chem., 2014)

(untitled) - Mohammadi Ziarani, G.; Lashgari, N.; Badiei, A. (J. Mol. Catal. A: Chem., 2015)

(untitled) - Gholamzadeh, P.; Mohammadi Ziarani, G.; Lashgari, N.; Badiei, A.; Asadiatouei, P. (J. Mol. Catal. A: Chem., 2014)

(untitled) - Yadav, G. D.; Nair, J. J. (Microporous Mesoporous Mater., 1999)

(untitled) - Wang, Y.; Wang, D.; Tan, M.; Jiang, B.; Zheng, J.; Tsubaki, N.; Wu, M. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Zolfigol, M. A.; Navazeni, M.; Yarie, M.; Ayazi-Nasrabadi, R. (Can. J. Chem., 2017)

(untitled) - Genies, C.; Mercier, R.; Sillion, B.; Cornet, N.; Gebel, G.; Pineri, M. (Polymer, 2001)

(untitled) - Wang, Y.; Huang, J.; Xia, X.; Peng, X. (J. Saudi Chem. Soc., 2018)

(untitled) - Saikia, M.; Saikia, L. (RSC Adv., 2016)

(untitled) - Sharghi, H.; Aboonajmi, J.; Aberi, M.; Shiri, P. (J. Iran. Chem. Soc., 2018)

(untitled) - Lokman, I. M.; Rashid, U.; Taufiq-Yap, Y. H. (Arabian J. Chem., 2016)

(untitled) - Sharghi, H.; Asemani, O. (Synth. Commun., 2009)

(untitled) - Sharghi, H.; ShahsavariFard, Z. (Helv. Chim. Acta, 2005)

(untitled) - Goli-Jolodar, O.; Shirini, F.; Seddighi, M. (RSC Adv., 2016)

Ionic liquids in synthesis - Wasserscheid, P.; Welton, T. (John Wiley & Sons, 2008)

(untitled) - Dhakshinamoorthy, A.; Asiri, A. M.; Alvaro, M.; Garcia, H. (Green Chem., 2018)

(untitled) - Welton, T. (Chem. Rev., 1999)

(untitled) - Gogoi, P.; Dutta, A. K.; Sarma, P.; Borah, R. (Appl. Catal., A, 2015)

(untitled) - Saikia, S.; Gogoi, P.; Dutta, A. K.; Sarma, P.; Borah, R. (J. Mol. Catal. A: Chem., 2016)

(untitled) - Dutta, A. K.; Gogoi, P.; Borah, R. (RSC Adv., 2014)

(untitled) - Shirini, F.; Abedini, M.; Seddighi, M.; Jolodar, O. G.; Safarpoor, M.; Langroodi, N.; Zamani, S. (RSC Adv., 2014)

(untitled) - Shirini, F.; Khaligh, N. G.; Akbari-Dadamahaleh, S. (J. Mol. Catal. A: Chem., 2012)

(untitled) - Mohammadi, K.; Shirini, F.; Yahyazadeh, A. (RSC Adv., 2015)

(untitled) - Shirini, F.; Yahyazadeh, A.; Mohammadi, K. (Chin. Chem. Lett., 2014)

(untitled) - Goli-Jolodar, O.; Shirini, F.; Seddighi, M. (Dyes Pigm., 2016)

(untitled) - Dutta, A. K.; Gogoi, P.; Saikia, S.; Borah, R. (J. Mol. Liq., 2017)

(untitled) - Khazaei, A.; Moosavi-Zare, A. R.; Firoozmand, S.; Khodadadian, M. R. (Appl. Organomet. Chem., 2018)

(untitled) - Tayebee, R.; Jomei, M.; Maleki, B.; Razi, M. K.; Veisi, H.; Bakherad, M. (J. Mol. Liq., 2015)

(untitled) - Khaligh, N. G.; Mihankhah, T.; Johan, M. R.; Ching, J. J. (J. Mol. Liq., 2018)

(untitled) - Amarasekara, A. S.; Owereh, O. S. (Ind. Eng. Chem. Res., 2009)

(untitled) - Amarasekara, A. S.; Wiredu, B. (Ind. Eng. Chem. Res., 2011)

(untitled) - Wiredu, B.; Amarasekara, A. S. (Catal. Commun., 2015)

(untitled) - Amarasekara, A. S.; Wiredu, B. (Catal. Commun., 2016)

(untitled) - Amarasekara, A. S.; Hasan, M. A. (Tetrahedron Lett., 2014)

(untitled) - Sharghi, H.; Shiri, P.; Aberi, M. (Catal. Lett., 2017)

(untitled) - Moosavi-Zare, A. R.; Zolfigol, M. A.; Noroozizadeh, E.; Salehi-Moratab, R.; Zarei, M. (J. Mol. Catal. A: Chem., 2016)

(untitled) - Noroozizadeh, E.; Moosavi-Zare, A. R.; Zolfigol, M. A.; Zare, A.; Zarei, M. (Can. J. Chem., 2017)

(untitled) - Moosavi-Zare, A. R.; Zolfigol, M. A.; Zarei, M.; Zare, A.; Khakyzadeh, V. (J. Mol. Liq., 2015)

(untitled) - Veisi, H.; Sedrpoushan, A.; Faraji, A. R.; Heydari, M.; Hemmati, S.; Fatahi, B. (RSC Adv., 2015)

(untitled) - Rostamnia, S.; Doustkhah, E. (Synlett, 2015)

(untitled) - Doustkhah, E.; Rostamnia, S. (Mater. Chem. Phys., 2016)

(untitled) - Sheng, X.; Zhou, Y.; Yang, Y.; Zhang, Y.; Zhang, Z.; Zhou, S.; Fua, X.; Zhao, S. (RSC Adv., 2014)

(untitled) - Guo, R.; Zhu, C.; Sheng, Z.; Li, Y.; Yin, W.; Chu, C. (Tetrahedron Lett., 2015)

(untitled) - Rodríguez-reinoso, F. (Carbon, 1998)

(untitled) - Naeimi, H.; Dadaei, M. (RSC Adv., 2015)

(untitled) - Liu, H.; Chen, J.; Chen, L.; Xu, Y.; Guo, X.; Fang, D. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Guan, Q.; Li, Y.; Chen, Y.; Shi, Y.; Gu, J.; Li, B.; Miao, R.; Chen, Q.; Ning, P. (RSC Adv., 2017)

(untitled) - Bhunia, S.; Banerjee, B.; Bhaumik, A. (Chem. Commun., 2015)

(untitled) - Mondal, S.; Patra, B. C.; Bhaumik, A. (ChemCatChem, 2017)

(untitled) - Pourmousavi, S. A.; Moghimi, P.; Ghorbani, F.; Zamani, M. (J. Mol. Struct., 2017)

(untitled) - Zhao, Y.; Wang, H.; Zhao, Y.; Shen, J. (Catal. Commun., 2010)

(untitled) - Liu, J.; Qiao, S. Z.; Liu, H.; Chen, J.; Orpe, A.; Zhao, D.; Lu, G. Q. (Angew. Chem., 2011)

(untitled) - Chang, B.; Guo, Y.; Yin, H.; Zhang, S.; Yang, B. (J. Solid State Chem., 2015)

(untitled) - Shuit, S. H.; Ng, E. P.; Tan, S. H. (J. Taiwan Inst. Chem. Eng., 2015)

(untitled) - Kondo, T.; Kameshima, T.; Kawai, T. (Chem. Lett., 2008)

(untitled) - Delbecq, F.; Takahashi, Y.; Kondo, T.; Corbas, C. C.; Ramos, E. R.; Len, C. (Catal. Commun., 2018)

(untitled) - Nongbe, M. C.; Ekou, T.; Ekou, L.; Yao, K. B.; Le Grognec, E.; Felpin, F.-X. (Renewable Energy, 2017)